2017
DOI: 10.1080/09712119.2017.1351369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bacillus subtilis B2A strain in laying hens challenged with Salmonella gallinarum: effects on egg production, egg quality, blood haptoglobin and targeted intestinal Salmonella shedding

Abstract: A total of 240 Hy-Line 40-week-old Salmonella-free layers were assigned to 5 dietary treatments composed of 12 replications, with 4 laying hens per replications in a 5-week experiment trial on laying hens challenged with Salmonella gallinarum. Dietary treatment comprised: (1) NC, basal diet; (2) PC, NC + oral S. gallinarum administration; (3) B8, PC + 0.1% Bacillus subtilis (10 8 cfu/g); (4) B9, PC + 0.1% B. subtilis (10 9 cfu/g) and (5) B10, PC + 0.1% B. subtilis (10 10 cfu/g). B. subtilis groups reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…While Mahdavi et al (2005) showed the effect on albumin quality, Xu et al (2006) proved increasing egg weight. On the other hand, Sobczak and Kozlowski (2015) and Hosseindoust et al (2018) did not find the results statistically significant. These results show that using probiotics is effective on egg weight and other traits but this could not be clearly demonstrated.…”
Section: According To the Total Values Shown Inmentioning
confidence: 84%
See 1 more Smart Citation
“…While Mahdavi et al (2005) showed the effect on albumin quality, Xu et al (2006) proved increasing egg weight. On the other hand, Sobczak and Kozlowski (2015) and Hosseindoust et al (2018) did not find the results statistically significant. These results show that using probiotics is effective on egg weight and other traits but this could not be clearly demonstrated.…”
Section: According To the Total Values Shown Inmentioning
confidence: 84%
“…The keywords searched according to the study protocol were laying hens, probiotic, B. Subtilis and egg weight. In this study, 37 studies were examined and 8 studies (Mahdavi et al 2005, Xu et al 2006, Zhang et al 2012, Amani et al 2013, Sobczak and Kozłowski 2015, Forte et al 2016b, Mazanko et al 2017, Hosseindoust et al 2018) that met the above conditions were selected and subjected to metaanalysis. In these studies, the difference between experimental and control groups was examined and none of them were statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteriophages are new types of animal antipathogen agents, which increase growth performance and improve animal health ( Adhikari et al, 2017 ; Hosseindoust et al, 2017 , 2018 ; Lee et al, 2021 ). In the current study, the preventive role of bacteriophage on gene expression of TLR4 and inflammatory cytokines were relatively higher in the jejunum rather than in the liver and muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of S. Gallinarum have frequently occurred in laying hen farms with considerable economic losses ( Seo et al, 2019 ). S. Gallinarum is a bird-specific pathogen with systemic infection initiating from the intestine and gradually infecting the other organs ( Hosseindoust et al, 2018 ). The laying hen immune response to control S. Gallinarum infection is not clearly understood, however, it has already been known that the enterocytes, cecal tonsils, and Peyer's patches are the first target of S. Gallinarum ( Setta et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation